Client-centered therapy - Broderson, Gene; Frank-McNeil, Julia; American Psychological Association ([United States] : American Psychological Association, 2007)
Nathaniel J. Raskin conducts a mock therapy session to illustrate the uses of client-centered therapy, a process that produces client self- discovery and actualization when the client's frame of reference is understood, accepted, and respected
For clinical training as well as for continuing education
Title from title screen
Project developers, John C. Norcross ... [et al.]
Narrator, Doug Fizel
Keywords: Client-centered psychotherapy; Mental health counseling